Exploration of Ethics of Public Accountants in the Values of the Banjar People's Philosophy of Life - Melinda Wijaya (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to explore the ethics of public accountants in the values of the Banjar people's philosophy of life using qualitative methods with literature studies. This study describes the philosophy of life of the Banjar people, namely waja to kaputing when actualized in the code of ethics of public accountants it can become noble values that can be used as pledges and principles for public accountants. The hope of this research is that the association of the public accounting profession has implications from this research so that it can incorporate and consider the values originating from the waja motto until kaputing is merged into the ethical practice of public accountants